(untitled) (Mustansiria Dental Journal, 2018)
An impression taking for edentulous ridge is the first step in the fabrication of the complete denture prosthesis. Various theories have been proposed by different authors as how to achieve an optimum impression in different ways. The purpose of this study was to compare the retentive forces required to dislodge maxillary complete denture bases fabricated by using different impression materials. Twenty completely edentulous patients were selected and three types of impression were made for each patient. The 1st group; final impression were made with zinc oxide eugenol "ZOE", 2nd group; final impression were made with light body addition silicone impression material and 3rd group; final impression were made with condensation impression material. Three stone casts were obtained for each patient and three denture bases were fabricated by short curing cycle, retention force examined and compared using strain gauge force transducer. Statistical analysis for the data collected using descriptive statistic, ANOVA and LSD, the result revealed that group A "Impression with ZOE" and B "Impression with addition silicone" show nearly the same results while group C "impression with condenation silicone" significantly less retentive force than that of group A and B. Retention of complete denture bases is greater in denture bases produced by zinc oxide eugenole final impression material than the other examined final impression materials.